Female outsiders in South Korea's dual labour market: Challenges of equal pay for work of equal value. (September 2020) - Lee, Sophia Seung-Yoon; Kim, Yuhwi
South Korea has a persistent gender pay gap despite its ratification of the Equal Remuneration Convention of the International Labour Organisation (ILO 100) and regulatory commitments to equal pay. This article identifies the extent to which the South Korean gendered dual labour market structure, notably the marked and gendered division between regular and irregular work, presents barriers to gender pay equality, and specifically to the implementation of equal pay principles. A layered examination of employment data, narrowing from aggregate statistics to occupations within two sub-industry groups, is used to examine how pay differences between women and men in work that is similar in content and educational requirements arise from their mode of employment, whether they are employed as regular or irregular workers. These structural divisions in the South Korean labour market are underpinned by a divided wage-setting system within which irregular workers are mostly excluded from benefits such as wage increases arising from seniority, and objective assessments of work value are lacking. In combination, these features help to explain why the principle of equal pay for equal work is breached and why limited progress has been made in meeting the requirements of equal pay for work of equal value.